Antimicrobial activity of blue mold (Penicillium italicum) Filtrates against some species of pathogenic bacteria - Fuad Hussain, Anaam (Diyala Journal of Medicine, 2024)
Background: Penicillium saprophytic species, which primarily consume organic biodegradable materials, is a common example of a fungal species. The preparation filtrates of Penicillium italicum, a saprophyte on citrus fruits frequently linked to post-harvest diseases in this crop, were included in the current investigation. Objective: This investigation aimed determine the most efficient culture medium for the production of antibacterial secondary metabolites. Patients and Methods: included identifying the growth medium for P. italicum and produce its metabolites through the use of gas chromatography-mass spectrometry (GC MS) for both solid-state fermentation filtrate (SSFF) and liquid fermentation filtrate (LFF). Additionally, the antimicrobial activity of the mold filtrate against certain pathogenic bacteria was assessed using the agar well diffusion method. Results: indicated that the biomass used for mold growth was heavier in SSFF than LFF, and according to the findings, the selective active isolate's crude filtrate from two duplicates of the P. italicum Yeast Extract Sucrose YES culture medium was 0.063 mg, while the crude extract from rotten orange (as a solid medium) containing P. italicum was 0.11 mg. Tetracosane and other substances with a track record of therapeutic activity were found in the two mold extracts, according to GC MS data. Overall, both SSFF and LFF demonstrated antibacterial activity against Klebsiella pneumonia, Escherichia coli, Acinetobacter baumannii, Pseudomonas aeruginosa and Staphylococcus aureus, with the inhibition zones± standard deviation (IZ± SD) being 24.7± 0.57, 18.2± 0.28, 26.3± 0.59, 21.6± 0.51, and 32.8± 0.21 (for SSFF) mm and 0.0, 12.3±0.57, 28.16±0.20, 19.3±1.15, and 28±0.2 (for LFF) mm, respectively. Conclusion: the filtrate of P. italicum from a natural medium (rotted orange) as a solid state fermentation was more weighted and gave many effective metabolites compared to what was produced by liquid fermentation on a synthetic medium, and both liquid and solid fermentation filtrates demonstrated efficacy against harmful bacteria.